2020
DOI: 10.2503/hortj.utd-150
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis in Response to Vernalization in Chinese Cabbage (<i>Brassica rapa</i> L.)

Abstract: Chinese cabbage (Brassica rapa L. var. pekinensis) is an economically and agriculturally significant leafy vegetable that is extensively cultivated throughout the world. Vernalization is exposure to prolonged cold that alters gene expression and accelerates a transition from the vegetative to reproductive phase. Premature bolting caused by exposure to cold inhibits head production and reduces the yield of Chinese cabbage, and developing a late bolting line is important for breeding. Therefore, it is critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…In B. rapa , H3K4me3 accumulation was found in the nucleation region of all four BrFLC paralogs before exposure to cold ( Kawanabe et al, 2016 ). During vernalization, accumulation of H3K27me3 within the nucleation region of all four BrFLC paralogs with decreased expression was observed ( Akter et al, 2020 ; Figure 1 ). After return to warm conditions, H3K27me3 accumulation spreads across the four BrFLC paralogs maintaining silencing ( Kawanabe et al, 2016 ; Akter et al, 2019 ; Figure 1 ).…”
Section: Histone Modification Triggers Epigenetic Silencing Of the mentioning
confidence: 99%
“…In B. rapa , H3K4me3 accumulation was found in the nucleation region of all four BrFLC paralogs before exposure to cold ( Kawanabe et al, 2016 ). During vernalization, accumulation of H3K27me3 within the nucleation region of all four BrFLC paralogs with decreased expression was observed ( Akter et al, 2020 ; Figure 1 ). After return to warm conditions, H3K27me3 accumulation spreads across the four BrFLC paralogs maintaining silencing ( Kawanabe et al, 2016 ; Akter et al, 2019 ; Figure 1 ).…”
Section: Histone Modification Triggers Epigenetic Silencing Of the mentioning
confidence: 99%
“…The sequence similarity between the paralogs ranged between 89.1% and 90.7%. A previous study showed that under cold treatment, BrVRN1a (Bra022376) is upregulated, while its paralogs BrVRN1b (Bra037544) and BrVRN1c (Bra001729) are downregulated [25,41]. We expected that knocking out any one paralog in Chinese cabbage would give comparable phenotypic results and therefore focused on BrVRN1a.…”
Section: Identification and Crispr-cas9 Mutagenesis Of Brvrn1 Genesmentioning
confidence: 99%
“…Sequences of the Chinese cabbage VRN1 genes (BrVRN1a, Bra022375, BrVRN1b, Bra037544, and BrVRN1c, Bra001729) were compared to find a region with matching sequences (Figures 1a and S1 and Table S1). Then, four sgRNAs were designed in the corresponding region to target the BrVRN1a (Bra022375) gene [25]. To construct a plasmid vector carrying four sgRNAs and the Cas9 cassette, we designed a multiplex CRISPR/Cas9 platform that allows the co-expression of four sgRNA modules targeting different sites of BrVRN1 in one binary vector (pAGM4723) using Golden Gate assembly (Figure 1b) [31].…”
Section: Sgrna Target Site Design and Vector Constructionmentioning
confidence: 99%
See 2 more Smart Citations